BIRT : a field guide to reporting - Peh, Diana (Eclipse series., 2006)
A new edition of this title is available, ISBN-10: 0321580273 ISBN-13: 9780321580276 The first in a two-book series about Business Intelligence and Reporting Technology, BIRT: A Field Guide to Reporting introduces reporting to a broad base of users. Built on the Eclipse platform, this exciting technology makes it possible for programmers and non-programmers to build and deploy complex reports with minimal effort. BIRT: A Field Guide to Reporting presents information about how to develop and customize reports of progressive complexity using BIRT Report Designer. This tool was designed from the ground up for Web applications and uses a Web page-oriented design metaphor in contrast to older banded report writers that were developed before the advent of the Internet. This unique approach to report creation makes BIRT an approachable and effective tool for developers of all levels. Report designs discussed include Listing reports that include sorting, grouping, and totals Summary reports, such as top N reports Charts, including pie, line, bar, and gauge charts Master-detail reports Other topics discussed include Understanding the technology Planning report designs Accessing data Laying out and formatting reports Building charts Enhancing reports with interactive viewing, shared libraries, and localized text Preparing reports for international data.